Extraction of Ge and synchronous activation of humic acid in germanium bearing lignite via oxidation leaching - Honghu Tang; Bingjian Liu; Xiongxing Zhang; Lijun Li; Zhenyue Zhang; Qingjun Guan (Fuel Processing Technology)
Germanium-bearing lignite was a crucial source for Ge extraction; however, existing methods focus on extracting Ge from lignite by-products, which overlooked its abundant organic matters. Effectively extracting valuable elements from lignite and fully utilizing its organic resources are still significant challenges. In this study, a novel processing of recovering Ge and synchronous extracting humic acids in germanium-bearing lignite via oxidation leaching was proposed. A Ge extraction recovery of 73.93 % was achieved using a L/S ratio of 10 and 5 % nitric acid at 90 °C for 30 min. The effects of nitric acid on the activation and depolymerization of lignite samples were also analyzed. The results demonstrated that HNO3 pretreatment significantly enhanced humic acid yield, increasing it from 28.73 % to 71.32 % in lignite. The mechanism of Ge oxidation leaching in lignite was investigated, which could be divided into four stages due to the migration and transformation behavior of germanium. In addition, a new technical route for the efficient and high recovery of strategic rare metals Ge and organic resources humic acid in lignite was proposed. The research establishes a foundation for the extraction of valuable metal elements and the efficient utilization of organic resources in lignite.